ENERGY-SAVING MATERIALS AND PROSPECTS OF THEIR APPLICATION TO BUILDING CONSTRUCTION - Tojiboyev Boburjon Tolibjonovich; Jalilova Gulnoza Xabibullo qizi (Western European Studies, 2024)
The article describes the results of experimental studies on the analysis and improvement of energy-saving materials and their application to newly constructed modern buildings and structures, as well as the existing methods of determining the thermal conductivity of these heat-insulating coatings.
Keywords: energy efficiency; heat insulating material; thermal conductivity